Effects of Deposition Potentials on the Morphology and Structure of Iron-Based Films on Carbon Steel Substrate in an Alkaline Solution - Soon-Hyeok Jeon; Geun-Dong Song; Do Haeng Hur (Advances in Materials Science and Engineering)
The purpose of this work is to investigate the effect of electrochemical deposition potential on the morphology and structure of iron-based films on the carbon steel in an alkaline Fe(III)-triethanolamine solution. The deposition potentials were controlled in the range from −1.05 to −1.23 VSCE for 1800 s at 80°C. Total amount of electric charge for electrodeposition process was increased with increasing deposition potential in negative direction. Pure magnetite films with a columnar and defect-free structure were deposited in the potential range from −1.05 VSCE to −1.11 VSCE. However, petal-like magnetite film containing ferrihydrite and iron was formed at −1.17 VSCE. At more negative potential of −1.23 VSCE, two distinct layers were observed: a porous outer layer containing ferrihydrite and goethite and a compact inner layer consisting of columnar metallic iron. In the potential range from −1.05 to −1.11 VSCE, the pure magnetite films gradually increased the thickness and decreased the surface roughness with an increase of the overpotential. The magnetite film deposited at −1.11 VSCE showed the most thick layer and smooth surface state.